Remote Prophylaxis of Social and Educational Adaptation of University International Entrants in Total Pandemic - Bulatova, Firaya F. (2021)
The relevance of the study is due to the trends of the global pandemic, which provoked an extremal transition of all areas of higher education to distance learning, as the only possible way to work with domestic and international entrants and students. In addition, the trends of the pandemic in the current educational environment also determine the special need to develop remote mechanisms for a prophylaxis approach to solving the problems of social and educational adaptation of international entrants – future University students. In this regard, this article is aimed at identifying the features of remote prophylaxis of social and educational adaptation of entrants. The article reveals the transformation of social and educational adaptation of international entrants in the global pandemic; defines the structure and content of remote prophylaxis of social and educational adaptation of international University entrants in the global pandemic. Based on the results of the research, the authors of the article substantiate the prophylaxis model of the educational and software complex for remote prophylaxis of social and educational adaptation of University international entrants. The effectiveness of the model is proved by the results of its use in the process of remote social and educational adaptation of University international entrants in the context of a global pandemic. The materials of the article have practical application and can be useful in the development and implementation of various methods and practices of social and educational adaptation of international entrants – future University students in the context of a global pandemic. It is recommended for University teachers and students, methodologists, curators, Tutors.